In Bimbingan Konseling Islam Dengan Metode Kisah Qurani Untuk Meningkatkan Religiusitas Lansia - Ade Dwi Maria Ningsih Ali Yamin; Kusnadi Kusnadi; Hartika Utami Fitri (ScidacPlus, 2023)
In old age, a person tends to experience a decline in fuction, both physically, psychologically and socially. Aging is an absolute thing, so the elderly should increase religiosity in their old age. Good religious philosophical development can make the elderly more calm in facing the realities of life, play an active role in life and feel valuable for the life they have. The method used in this study is the Quranic Story method. The purpose of choosing the Qur’anic Story wthos is easy to understand, illustrated based on the results of individual understanding, and easy to touch the heart. The research method. Data collection techniques used in this study were interviews, observation, and documentation. The results of this study are that prior to the implementation of counseling activities based on the religiosity group of the elderly, it was still low, seen from the ritual or worship sctivities of the elderly, the interest of the elderly in learning, practicing, and believing in religious velues. The group guidance process using the Quranic Story method, the subjects showed a change in their awareness of the importance of religious values, especially in old age, in the religiosity of the elderly there are changes toward a better direction in terms of worship and behavior